Jean-Paul Sartre: Analyzing Human Existence Through the Lens of Existentialism - Paisal Siregar; Hasnah Nasution; Syukri Syukri (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to explore Jean-Paul Sartre’s existentialist perspective on human existence, emphasizing radical freedom and the responsibility of individuals in defining their own meaning in life. The research investigates how Sartre's concept of existentialism positions humans as autonomous subjects in constructing their essence. Methodology: This study employs a qualitative descriptive-analytical approach, utilizing a literature review method. The primary sources include Sartre’s major works, such as Being and Nothingness, along with secondary analyses from contemporary existentialist scholars. Data are analyzed through content analysis to examine Sartre’s views on freedom, responsibility, and self-determination. Main Findings: The findings reveal that Sartre perceives human existence as devoid of inherent meaning, compelling individuals to create their own purpose through conscious choices. His concept of bad faith illustrates the tendency to escape from existential responsibility, whereas authentic existence requires embracing radical freedom. Sartre’s framework highlights the psychological tension between autonomy and existential anxiety. Novelty/Originality of this study: This study offers a fresh interpretation of Sartre’s existentialism by relating his views to contemporary issues of identity, freedom, and personal responsibility. It extends the discussion of existentialist ethics in modern society and provides a deeper analysis of Sartre’s influence on current philosophical and social discourses on human autonomy.